Partially bio-based poly(amide imide)s by polycondensation of aromatic diacylhydrazides based on lignin-derived phenolic acids and aromatic dianhydrides: synthesis, characterization, and computational studies - Kuhire, Sachin S.; Sharma, Pragati; Chakrabarty, Suman; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Two new bio-based diacylhydrazide monomers, namely, 4,4-(propane-1,3-diylbis(oxy))bis(3-methoxybenzohydrazide) and 4,4-(propane-1,3-diylbis(oxy))bis(3,5-dimethoxybenzohydrazide) were synthesized starting from lignin-derived phenolic acids, namely, vanillic acid and syringic acid. A series of poly(amide imide)s was synthesized by polycondensation of these diacylhydrazide monomers with commercially available aromatic dianhydrides. Poly(amide imide)s showed inherent viscosity in the range 0.44-0.56 dLg(-1) and exhibited good solubility in organic solvents. Poly(amide imide)s could be cast into transparent, flexible, and tough films from their N,N-dimethylacetamide solutions. Poly(amide imide)s showed 10% weight loss in the temperature range 340-364 degrees C indicating their good thermal stability. Glass transition temperature (T-g) of poly(amide imides)s were measured by DSC and DMA which were in the range 201-223 degrees C and 214-248 degrees C, respectively. The T-g values of poly(amide imide)s were dependent on the number methoxy substituents on aromatic rings of diacylhydrazide monomers. Molecular dynamics simulation studies revealed that chain rigidity is the dominant factor for observed trends in T-g. (c) 2017 Wiley Periodicals, Inc.
Keywords: Biobased Polymers; Computational studies; Glass-transaction temperature; lignin; Monomers; Plant oils; Polyimide; Reneable resources; Renewable resources; Step-growth polymers; structure-property relations; Sustanaible Polymers; Thermal night; Thermosetting resins; Vanillin

Synthesis, characterization, crystal structure, in silico and computational studies on a novel Schiff base derived from α-chlorocinnamaldehyde and 4-aminoantipyrine - Adimudo, Hillary Chijioke; Agu, Chidike Justus; Okenyeka, Obinna U.; Eddy, Nnabuk O.; Dim, Ebubechukwu Nnamdi; Dege, Necmi; Bonardd, Sebastian; Vanka, Kumar; Ibezim, Akachukwu; Idika, Digbo Iku; Diaz, David Diaz; Obasi, Nnamdi Lawrence (Journal of Molecular Structure, 2023)
Schiff base, 4-(((1E,2Z)-2-chloro-3-phenylallylidene)amino)-1,5-dimethyl-2-phenyl-1,2 -dihydro-3H-pyrazol-3-one (1) was synthesized by condensation reaction of 4-aminoantipyrine and & alpha;-chlorocinnamaldehyde. The compound was characterized using Fourier-transform infrared spectroscopy (FT-IR), ultraviolet (UV)-visible spectroscopy, proton and carbon nuclear magnetic resonance spectroscopy (1H/13C NMR) and single-crystal X-ray diffraction analysis (SC-XRD). Density functional theory (DFT) was used to compute molecular parameters and also compared them with experimental data. The X-ray diffraction data revealed that the compound crys-tallizes as a monoclinic crystal system with a space group of C2/c and Z = 8, and is stabilized by C12-H12MIDLINE HORIZONTAL ELLIPSISO1, and C8-H8AMIDLINE HORIZONTAL ELLIPSISO1 intramolecular hydrogen bonds. The presence of a distinctive azomethine C = N bond length N3-C12 of 1.283(3) & ANGS;, and 1640 cm-1 stretching vibration in the FT-IR spectrum are evidence of the formation of a Schiff base. The computational result indicates that the ionization energy (IE), and electron affinity (EA) values for the molecule are 4.025 and 2.110 eV, respectively. The positive value of EA suggests that the addition of an electron to the molecule would be an exothermic process. The evaluated energy is relatively low and is an expression of the ease of electron transfer from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). Hirsfeld surface map over dnorm and curvedness surface indicated the presence of 7C-7C stacking while the shape factor index suggests donor and acceptor intermolecular C-H-7C. Analysis of Hirsfeld surfaces concerning the fingerprint indicated a minimal contribution from the de -di pair and reveals H–H as a major contribution to the Hirsfeld surface. However, the molecular packing did not confirm H–H as a significant contributor the packing. Docking calculations on the compound showed average theoretical binding energies toward aromatase (-5.99 & PLUSMN; 0.34 kcal/mol) and fibroblast growth factor receptor (FGFR) (-17.57 & PLUSMN; 6.85 kcal/mol), indicating binding interactions with both protein targets.
Keywords: Computational studies; molecular modeling; Schiff base; X-ray crystallography